Follow Up on Simple (Closed) Extraction of Fractured Maxillary Canine Teeth in Domestic Ferrets (Mustela putorius furo) - Primožič, Pia Kristina; Žagar, Žiga; Šmalc, Klemen; Račnik, Joško; Švara, Tanja; Nemec, Ana (Frontiers in Veterinary Science, 2021)
Fractured canine teeth (especially maxillary canine teeth) are common in domestic ferrets (Mustela putorius furo). We evaluated (detailed oral/dental and radiographic examination under general anesthesia) 18 domestic ferrets affected by 23 complicated crown fractures of periodontally healthy permanent maxillary canine teeth over a 2-year period. Average age of the ferrets at the time of diagnosis was 2.6 years. Only 3 teeth were discolored on clinical examination. Out of 23 teeth, 22 were radiographically evaluated. No radiographic evidence of endodontic disease was observed in 11/22 canine teeth. Inflammatory root resorption was observed in 5/22, periapical lucency in 5/22 teeth, apical widening of periodontal ligament space in 6/22 teeth, and failure of the pulp cavity to narrow in 3/22 teeth. All animals were treated by simple (closed) extraction of the affected teeth. Histological examination of 8 teeth was performed. Pulp appeared histologically vital in 5 (3/5 showed no radiographic evidence of endodontic disease), pulpitis was diagnosed in 2 (both without radiographic evidence of endodontic disease) and pulp necrosis in 1 case (dental radiographs revealed apical widening of periodontal ligament space and failure of the pulp cavity to narrow). All extraction sites healed uneventfully by the 2-week recheck examination. Long-term follow-up revealed development of post-extraction upper lip entrapment with mandibular canine tooth in 8 out of 18 ferrets, which appeared clinically irrelevant. According to clients 7 out of 18 ferrets showed an improved quality of life. Simple tooth extractions are warranted in ferrets affected by complicated crown fracture of the maxillary canine teeth.